Helichrysum emodi (Gnaphalieae: Asteraceae), a new species from the Indian Himalaya - Singh, Sunit; Mehta, J.p.; Kumar, Anant (Phytotaxa, 2024)
Helichrysum emodi (Gnaphalieae: Asteraceae) is described as new to science from Madhmaheshwar valley of Uttarakhand, India. Morphologically it resembles H. cutchicum and H. kashgaricum, but differs from these two species in having broad, sub-cordate to semi-amplexicaule leaf base with obtuse apex, shape of phyllaries, and absence of female florets, respectively. A detailed morphological description and illustration of H. emodi, together with pollen and habitat photographs and a key to the species of Helichrysum occurring in India are provided for the species identification.